(untitled) (Universal International Scientific Journal, 2026)
This article psychologically analyzes the role of social consciousness and gender views in the formation of values ​​related to family and marriage among medical students. It highlights socio-psychological factors that influence young people’s perceptions of family, expectations from marriage, the distribution of family roles, and the formation of gender stereotypes.